2015
DOI: 10.21605/cukurovaummfd.242775
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye İnşaat Endüstrisindeki İnovasyon Düzeyinin İnşaat Mühendisliği Penceresinden Görünümü

Abstract: Özetİnovasyon; yeni veya önemli ölçüde değiştirilmiş ürün (mal ya da hizmet) veya sürecin; yeni bir pazarlama yönteminin; ya da iş uygulamalarında, iş yeri organizasyonunda veya dış ilişkilerde yeni bir organizasyonel yöntemin uygulanmasıdır. Bir ülkenin rekabet gücü, ülke endüstrilerinin yenilik ve gelişim yeteneğine, dolayısıyla inovasyona verdiği öneme bağlıdır. İnovatif organizasyonları olmayan toplumların gelişimleri sınırlı olup, bu toplumlar geri kalmaya ve yoksulluğa mahkûmdurlar. Ekonominin en can alı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Since innovation is a very difficult and a painful process in the construction sector, companies generally do not want to take risks. Nanotechnology is seen as one of the most important technologies that will drive innovation in the construction sector (Genç et al, 2016). In some studies, insufficient R&D investment is presented as one of the weaknesses of the sector (Forbes and Ahmed, 2011).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since innovation is a very difficult and a painful process in the construction sector, companies generally do not want to take risks. Nanotechnology is seen as one of the most important technologies that will drive innovation in the construction sector (Genç et al, 2016). In some studies, insufficient R&D investment is presented as one of the weaknesses of the sector (Forbes and Ahmed, 2011).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The Turkish construction sector is incompetent in innovation, and the government needs to lead the industry in innovation and R&D. It is seen through studies that there is a lack of trust in the construction sector against new ideas and innovation. It is necessary to establish legal obligations and standards, and ultimately create an awareness of innovation (Genç et al, 2016). It is important to go beyond the financial incentives and supports for innovation and should take steps to create a culture of innovation in the long run.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…When we compare the Turkish construction sector with other sectors, it is observed that it is slow in terms of innovative trends, and technology-oriented innovation development and adaptation remains to be seen. According to the research results of Genç et al, only 14.8% of Turkey construction sector professionals are sufficient with innovation level in the construction sector [1]. However, in today's market conditions, innovating and adapting to it is critical for sustainable firm performance.…”
Section: Introductionmentioning
confidence: 99%